2022
DOI: 10.1371/journal.pone.0266333
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, intensity of infection and associated risk factors of soil-transmitted helminth infections among school children at Tachgayint woreda, Northcentral Ethiopia

Abstract: Background Soil-transmitted helminths (STH) are one of the most common infections affecting underprivileged populations in low- and middle-income countries. Ascaris lumbricoides, Trichuris trichiura, and hookworm are the three main species that infect people. School children are the most vulnerable groups for STH infections due to their practice of walking and playing barefoot, poor personal hygiene, and environmental sanitation. However, evidence is limited in the study area. So, this study aimed to assess th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 36 publications
1
9
1
2
Order By: Relevance
“…Fingernail biting also increase the risk of soil transmitted helminth infection. These results were similar to those in a study carried out in Tachgayint Woreda in Northcentral Ethiopia, where fingernail status was found to be significant predictors of STH infection [ 30 ].…”
Section: Discussionsupporting
confidence: 90%
“…Fingernail biting also increase the risk of soil transmitted helminth infection. These results were similar to those in a study carried out in Tachgayint Woreda in Northcentral Ethiopia, where fingernail status was found to be significant predictors of STH infection [ 30 ].…”
Section: Discussionsupporting
confidence: 90%
“…As a result, vast numbers of eggs are discharged into the human environment daily. Furthermore, the hard nature of these eggs to resist adverse environmental conditions more than other STHs can contribute to sustaining the transmission cycle for a longer period [ 37 ]. A study was conducted on 207 adults and 179 children visiting health facilities of Ghazni and Parwan provinces of Afghanistan.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to our study, increased moderate-heavy intensity STH infections have been reported from Myanmar [ 44 ], Malaysia [ 45 ], Cameroon [ 46 ], and Rwanda [ 47 ]. Contrary, decreased moderate-heavy intensity STH infections have been reported from India [ 48 ], Ethiopia [ 37 ], and Nigeria [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…This public health problem remains unsolved (Tadege et al, 2022). Worms can be transmitted in various ways, including food and drink contaminated with worm eggs or soil (Eyayu et al, 2022). The activities of mining workers have been classified as the highest risk group for helminth infections (Tuuk et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, identifying a miner's worm parasitic eggs can be used to know if STH has contaminated the environment (Wikurendra et al, 2021). Several studies have examined soil helminth through feces or nails (Eyayu et al, 2022;Khan et al, 2022;Tuuk et al, 2020;Wikurendra et al, 2021), but there is still insufficient data for comparison examination of the two methods. Therefore, this study aimed to detect the prevalence and intensity of infections caused by parasitic worms by comparing nail and fecal examinations among mining workers.…”
Section: Introductionmentioning
confidence: 99%